MUSLIMS CONSUMERS’ TRUST AND DEPENDENCE ON FOREIGN HALAL LOGO - Shofiyyah Moidin; Siti Nurfatin Hazwani Romji; Muhammad Syukri Mohd Ashmir Wong; Norazlina Mamat; Nur Hafizah Harun; Farrah Payyadhah Borhan (Journal of Islamic, Social, Economics and Development, 2023)
As the emergence of halal keeps on proliferating at the international level every now and then, the awareness of halal foods' importance also increases among the consumers. Due to that, the demand for halal food also grows expeditiously regardless of Muslim or non-Muslims consumers all around the world. Thus, the halal logo becomes consumers’ cue in determining the halal status of a food product. However, various halal logos in the market and forged halal logo issues cause confusion in consumers and lack of trust and dependence on the foreign halal logo other than the Malaysian halal logo. The purpose of this study is to identify trust on foreign halal logos on food products among Muslims in Kampung Pinang. A quantitative method has been applied to conduct this study with 325 samples of the survey from Muslim consumers, and the result has been analyzed using descriptive analysis. The result revealed that consumers positively have trust, and their dependence on the foreign halal logos is good, but their dependency can change according to the presence of locally produced food products. These findings from this study are expected to maintain the level of trust and to steer clear the consumers of having no dependence at all on the recognized foreign halal logo as well as open more opportunities on the future study regarding the foreign halal logo.